Geographic patterns of vascular plant diversity at continental to global scales - Barthlott, Wilhelm; Hostert, Alexandra; Kier, Gerold; Küper, Wolfgang; Kreft, Holger; Mutke, Jens; Rafiqpoor, M. Daud; Sommer, Jan Henning (ERDKUNDE, 2007)
Documenting and understanding patterns of biodiversity is a central issue in biogeography and macroecology. Knowledge about the distribution of biodiversity is also a central prerequisite for its sustainable use and conservation. Due to a greater availability of distribution data, methodological advances, and software tools, important progress has been made during the last decade to map broad-scale geographic gradients of plant species richness and endemism at continental to global scales. In this paper, we provide an overview about recent advances made in this field. We present studies that analyze globalscale diversity patterns of gymnosperms and all vascular plants. Exemplarily for the model continent Africa, we show how biogeographic data can be used to develop broad-scale conservation strategies.